The angel Esmeralda [compact disc, unabridged] : nine stories - DeLillo, Don (Simon & Schuster Audio, 2011)
Set in Greece, the Caribbean, Manhattan, a white collar prison, and outer space, these nine stories are a mesmerizing introduction to Don DeLillo's iconic voice, from the rich, startling, jazz-infused sentences of his early work to the spare, distilled, monastic language of the later stories.